Physicochemical and sensory characteristics of meatless nuggets of boiled chickpea and in combination with oyster mushroom - Moorthi, Pravinraj; Abu Bakar, Che Abdullah; Ismail-Fitry, Mohammad Rashedi; Ismail, Ishamri (Persatuan Biologi Gunaan Malaysia, 2022)
This study aimed to develop meatless nuggets (MN) using different substitutions of chickpea and oyster mushrooms as key ingredients. Four different meatless nuggets which were control (100:0), MN70 (70:30), MN40 (40:60), and MN10 (10:90) with different ratios of boiled chickpea to mushroom were formulated in this study. A significantly (p<0.05) higher carbohydrate, protein, fat, and crude fiber contents were observed with the increasing chickpea substitution. Nuggets prepared with chickpea and mushroom proteins met the standard of protein source for the nutrient reference value as well as the source of good fiber. However, results found that a significant (p<0.05) lower cooking yield and higher cooking loss were recorded in the sample substituted with the maximum ratio of mushroom (MN10). Likewise, textural properties such as hardness, springiness, cohesiveness, and chewiness increase (p<0.05) with mushroom substitution. Substitution with higher chickpea tends to increase lightness (L*) and yellowness (b*) of control. The panelists for the sensory evaluation presented that MN40 containing an almost equal substitution of chickpea to mushroom had a better sensory mean score. However, substitution by these ingredients was the averagely scored by the panelists. Hence, nuggets with a 40:60 ratio of chickpea to mushroom were considered the ideal formulation for manufacturing meatless nuggets.